Developing Listening Skills through Lesson Study at Gagas Ceria Elementary School, Bandung Indonesia - Juliasih Hizbar, Juliasih (International Conference on Elementary Education, 2020)
The development of studentâ€™s listening skills is very important because listening skills are one of the process of receiving information or verbal messages. The learning process involves many listening activities such as listening to teacherâ€™s instructions, group discussions and others. Based on these situations, teachers need to stimulate the development of studentâ€™s ability in listening according to their age. GagasCeria Elementary School teachers recognize the importance of listening skills in the learning process. Therefore, when conducting lesson study, which are routinely performed at the school, the development of students’ listening skills is one of the most considered in designing learning activities. An observation on three lesson study activities that implemented listening skill development had conducted. The focus of the observations are the method used to develop listening skills, the form of teacher intervention and activities to improve studentâ€™s abilities and the influence of teacherâ€™s experience on the stimulation performed. Based on observation made, it is found that: Listening skills should be developed from lower grade, In lower grades, teachers usually strengthen basic listening skills more often. Whereas in upper grade, listening skills are used to communicate effectively between students, Models are very influential and have an impact on children. The teacher should be a role model in class for students, Teacherâ€™s experience affects the development and stimulation of listening skills in the classroom, The form of teacherâ€™s intervention in developing listening skills in the classroom is to design learning process that can develop listening skills